2016
DOI: 10.1007/s00330-016-4304-8
|View full text |Cite
|
Sign up to set email alerts
|

A noise-optimized virtual monochromatic reconstruction algorithm improves stent visualization and diagnostic accuracy for detection of in-stent re-stenosis in lower extremity run-off CT angiography

Abstract: • The impact of noise-optimized virtual monochromatic imaging on stent visualization was assessed. • Virtual monochromatic imaging significantly improves stent lumen visualization and diagnostic confidence. • At 80 keV diagnostic performance for detection of in-stent restenosis was increased. • 80 keV virtual monochromatic images are recommended for stent evaluation of lower extremity vasculature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…However, a recent study found 70 and 80 keV achieved optimal image quality with the use of DECTA in 31 patients with 45 stents. It was stated that increasing keV to over 80 (90-150 keV) did not show any improvement in either image quality or diagnostic confidence (5). Studies that have evaluated lower extremities with DECT found that optimal image quality falls between 55 to 70 keV (13,19,20).…”
Section: Almutairi Et Al Dual Energy Ct Angiography In Peripheral Armentioning
confidence: 99%
See 2 more Smart Citations
“…However, a recent study found 70 and 80 keV achieved optimal image quality with the use of DECTA in 31 patients with 45 stents. It was stated that increasing keV to over 80 (90-150 keV) did not show any improvement in either image quality or diagnostic confidence (5). Studies that have evaluated lower extremities with DECT found that optimal image quality falls between 55 to 70 keV (13,19,20).…”
Section: Almutairi Et Al Dual Energy Ct Angiography In Peripheral Armentioning
confidence: 99%
“…Huang et al reported an improvement of correction with DECT (4). In a recent study by Mangold et al, reduction of blooming artifacts in imaging peripheral arterial stents with improved image quality was achieved when 70 or 80 keV was used (5). Stent lumen visibility for small stents was reported in a phantom study at high keV when the third generation of dual-source CT and DECT was used (6).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a convenient, safe, accurate, and economical tool, computed tomography angiography (CTA) is broadly utilized in clinical practice, and has become a predominant substitute for digital subtraction angiography in preoperative diagnosis and postoperative assessment of peripheral arterial disease (1)(2)(3). Iodinated contrast media (CM) can enhance the visualization of vessels and improve the contrast of the region of interest against adjacent tissue, which is especially necessary for CTA (4).…”
Section: Introductionmentioning
confidence: 99%
“…2 -test. Analysis of variance was applied in the analysis of the vascular attenuation, noise, SNR, and CNR of A1 and B1-B10.…”
mentioning
confidence: 99%